Mathematical model of the 9th version Universal modeling method: features and results of identification - A. A. Drozdov; Yu. B. Galerkin; O. A. Solovyeva; K. V. Soldatova; A. A. Ucehovscy (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The Universal modeling method is a complex of computer programs for calculating the characteristics and optimal design of centrifugal compressors based on mathematical models of efficiency and head. Practical experience allows improving the mathematical models that underlie the Method. Determining the non-incidence inlet in a blade cascade is an important part of calculating the compressor gas-dynamic characteristics. In the 8th version of the Universal modeling method, a formula is used to calculate the direction of the critical stream line, containing an empirical coefficient X. The practice of application has shown that the value of the empirical coefficient changes the amount of losses in the impeller in off-design flow rates. A new scheme for modeling velocity diagrams is proposed. It is made for the stage operation mode corresponding to the zero incidence angle. The successful use of the model for the impeller made it possible to extend it to the vane diffuser and return channel. Several other improvements are made too. A new mathematical model is developed for calculating the flow parameters in the exit nozzles of centrifugal compressor stage. The mathematical model for calculating the flow parameters in the vaneless diffusers is modernized. The applicability boundary of the new model is expanded to a range of diffusers of low consumption stages with a relative width of up to 0,006. The resulting mathematical model is identified by the test results of two family model stages and plant tests of industrial compressors